(untitled) (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2024)
Contamination of natural water resources by heavy metal ions poses significant environmental and health risks to humans. Reversible polymeric adsorbents, especially those based on cellulose, are of great interest for addressing this problem. This paper investigates the conditions for grafting maleic anhydride onto cellulose macromolecules and the ability of the obtained product to adsorb heavy metals.